rgentine Catholic crowds in the first half of the 20th century. Religion, politics and mass society (Quinto Sol, 2015)
The article reviews the theoretical and historiographical interpretations on the processes of mobilization and formation of Catholic crowds in Argentina in the first half of the 20th century. The performative effects of the so-called “classic paradigm” of secularization are analyzed and the need arises to relocate the contributions of the political perspective, developed in the context of the 1980s, in a broader explanatory framework, capable of incorporating the contributions of recent social and cultural history. For this purpose, an approach is outlined that, based on the concept of the multitude, aims to bring different dimensions of the phenomenon into dialogue, underlining its polyhedral nature and its political and/or ideological irreducibility.
Keywords: Catholic Church; secularization; mobilization; Catholicism; modernity